Extent of male involvement and associated factors in antenatal care service utilization in Bench Sheko zone, Southwest Ethiopia: A community-based cross-sectional study - Mekonen, Mengistu; Shifera, Nigusie; Bogale, Biruk; Assefa, Ashenafi (Frontiers in Global Women's Health, 2022)
Background: In many low and middle-income countries (LMIC), men are the key decision-makers and chief providers, often determining women's access to economic resources and maternal health services. Despite the important role of men in maternal health care, the involvement of male partners in maternal and child health in LMIC, including Ethiopia, is low. Objectives: To assess the extent of male involvement and associated factors in antenatal care (ANC) service utilization in Bench Sheko zone, South-West, Ethiopia. Methods: A community-based, cross-sectional study was conducted in the Bench Sheko zone from February to May 2021. A multistage sampling technique was employed to select study participants. Variables with p-values <0.25 in binary logistic regression were selected as candidates for multiple logistic regression to determine independent factors associated with male involvement adjusting for socio-demographic, health service, personal, environmental, and knowledge-related factors. Results: A total of 816 men took part in the study, with a 98.2% response rate. The prevalence of male involvement in ANC utilization was 38.2%. In multivariate analyses, residence (urban), age (25-34), education (diploma and above), income (≥2500ETB), and high knowledge of the advantages of ANC were shown to be positively associated with male involvement in ANC utilization. Conclusion: Male involvement in ANC utilization was low. Considering the importance of male involvement in maternal health care, we advocate for policies and strategies that can improve knowledge of the advantages of ANC among men and can enhance their engagement in maternal care. Special attention should be given to younger partners and those partners who live in rural areas.